Comparative Validation of NASA POWER and ERA5 Satellite-Based Meteorological Data Using BMKG Observations in Bandar Lampung, Indonesia - Ayu Aprilia; Alka Budi Wahidin; Ahmad Faruq Abdurrahman; Surya Prihanto; Yusril Al-Fath (Jurnal Info Sains : Informatika dan Sains, 2025)
This study aims to evaluate the performance of satellite reanalysis data from NASA POWER and Copernicus ERA5. BMKG data was used as a reference to compare the accuracy of satellite reanalysis data. Data was specifically collected from Lampung Province for the years 2022 to 2024. The data compared includes temperature, humidity, wind speed, and rainfall. The temperature data from ERA5 provided consistent and accurate results with a MAE of 1.82 and an r of 0.59. POWER showed commendable performance in capturing relative humidity with a MAE of 5.05% and an r of 0.33. For the wind speed variable, both models showed underestimation for Copernicus and overestimation for NASA POWER. For rainfall (RR), both models failed to predict extreme weather. NASA POWER showed an MAE of 8.59 mm/day and Copernicus showed a value of 7.68 mm/day for the rainfall variable. Future research can focus on bias correction results and machine learning to overcome the challenges faced by satellite data in predicting rainfall.